2004
DOI: 10.1289/ehp.6524
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal bone composition in female juvenile American alligators from a pesticide-polluted lake (Lake Apopka, Florida).

Abstract: Reproductive disorders have been found in pesticide-exposed alligators living in Lake Apopka, Florida (USA). These disorders have been hypothesized to be caused by exposure to endocrinedisruptive estrogen-like contaminants. The aim of this study was to expand our analysis beyond previous studies by investigating whether bone tissue, known to be affected by sex steroid hormones, is a potential target of endocrine disruptors. Long bones from 16 juvenile female alligators from Lake Apopka (pesticide-contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 36 publications
1
30
1
Order By: Relevance
“…In recent years, several studies evaluated the impact of CYP and END formulations on the ISs of non-target organisms; these studies demonstrated that concentrations of these agents commonly applied in agriculture generated adverse effects in different wild species (Pushpanjali et al 2005;Velisek et al 2006;Beldomenico et al 2007;Bachetta et al 2011). Many studies have been made in order to assess exposure to pesticides in different crocodilian species at different life stages, including viable and non-viable eggs (Crain et al 1999;Milnes et al 2004), juveniles Lind et al 2004) and adults (Crain et al 1998). However, there have been few studies that evaluated the effects of pesticides on their ISs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies evaluated the impact of CYP and END formulations on the ISs of non-target organisms; these studies demonstrated that concentrations of these agents commonly applied in agriculture generated adverse effects in different wild species (Pushpanjali et al 2005;Velisek et al 2006;Beldomenico et al 2007;Bachetta et al 2011). Many studies have been made in order to assess exposure to pesticides in different crocodilian species at different life stages, including viable and non-viable eggs (Crain et al 1999;Milnes et al 2004), juveniles Lind et al 2004) and adults (Crain et al 1998). However, there have been few studies that evaluated the effects of pesticides on their ISs.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this observation remain to be clarified. Altered bone mineral density was reported in studies of additional species of free-ranging wildlife, including the skulls and bacula of East Greenland polar bears (Ursus maritimus) (Sonne et al, 2004(Sonne et al, , 2006, the jaws and radius of Baltic gray seals (Halichoerus grypus) (Lind et al, 2003), and the tibias and femurs of American alligators (Alligator mississippiensis) (Lind et al, 2004). Cortical bone mineral content of femurs of gulls from Great Lakes colonies was significantly lower than that of gulls from the marine reference colony.…”
Section: Locationmentioning
confidence: 94%
“…The pQCT method has been used, with modifications, in previous studies (Lind et al, 2000(Lind et al, , 2004Lundberg et al, 2006). Before analysis, the bones were placed in plastic test tubes filled with Ringer solution (1 L contains 0.3 g Tris; 0.24 g CaCl 2 (H 2 O); 0.4 g KCl; and 2.05 ml 1 M HCl; pH 7.4).…”
Section: Peripheral Quantitative Computed Tomography (Pqct)mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of applied studies, monitoring of pest and invasive species (Fuchs et al., 2004; Halley et al., 2005; Harrison et al., 1993; Monaenkova et al., 2015; Soné, Mori, Ide, Setoguchi, & Yamanouchi, 1995; Tarver et al., 2006), interaction between hosts and parasites (Greco et al., 2010; Schwabe et al., 2014), forensic entomology (Johnson et al., 2012), and ecotoxicological research (Brinkmann et al., 2016; Holliday & Holliday, 2012; Lind et al., 2004; Pigneret et al., 2016; Yunusa, Braun, & Lawrie, 2009) have been also benefited greatly from this technique so far.…”
Section: Perspectives and Final Considerationsmentioning
confidence: 99%